INFLUENCE OF A SCIENCE CAMP BASED ON ACTIVE LEARNING ON STUDENTS - Ahmet TEKBIYIK (Fırat University, 2019)
The purpose of this study is to examine the effects of the project titled “An Entertaining Discovery of the Mysterious World: Summer Science Camp II”, which was conducted within the scope of the TUBITAK 4004 Nature Education and Science Schools project, on students. 48 students who had completed the primary education 7th grade participated in the project. To determine the effects of the project on the participants, semi-structured interviews, diaries, Scientific Attitude Scale, “Science Lab Attitude Scale”, and the letters written by the participants at the end of the camp were used. The activities conducted at camp were aimed at enabling students to comprehend basic scientific phenomena in the fields of physics, chemistry, biology, mathematics, and ecology. Furthermore, activities about personal, academic, and professional development of students were conducted together with a guidance specialist included in the project. The interviews demonstrated that students generally had quite positive views concerning the activities. It was seen that student motivation was satisfactory during the camp period. Based on the data obtained from the Scientific Attitude Scale, it can be said that a statistically significant improvement took place in the attitudes of primary education students participating in summer science camp about science and science lab at the end of the camp in comparison to the pre-camp period. When all evaluations are taken into consideration, it is seen that participants completed camp period with positive cognitive and affective acquisitions. In the light of the contributions of the project to students, it can be recommended to generalize these kinds of science camps for different groups, places, and disciplines within the body of universities, and to encourage implementation and participation.